Impact on wage income to the level of training of higher education in Colombia during 2013-2014. Perspective from the economics of education (2016)
In a world globalization education has taken one important role, of course it has been considere one factor of production, which it has one impact over percapita income and economics growth rate of one country. The objective of te present work is to analyse and to describe the impact that that has the educations level over wages colombian people on the job market in the years 2013 and 2014. With the end to keep the objective it make one statistical test descriptive of the figures that were gave Observatory Job for Education, then to value one Model of Regression Logistics Nominal, whichit can to show the correlation between the variables: training of Human Capital (Education) and incomes level. This work is divide in four parts: the first part is the introduction where to explain te importance of the training of Human Capital. The second part has two aspects: development of the economics theory which to appoach the Capital Humans Theory and the statistics figures of the Graduates Colombians with yorus respective remuneration in the job market, like wise will have one analysis of the result of the nominal regression.